Perceptions on donated human milk and human milk banking in Nairobi, Kenya. Issue 4 (26th July 2019) - Kimani‐Murage, Elizabeth Wambui; Wanjohi, Milka Njeri; Kamande, Eva Watiri; Macharia, Teresia Njoki; Mwaniki, Elizabeth; Zerfu, Taddese; Ziraba, Abdhalah; Muiruri, Juliana Waithera; Samburu, Betty; Govoga, Allan; Kiige, Laura Wangui; Ngwiri, Thomas; et al.
Abstract: Donor human milk (DHM) is recomended as the best alternative when use of mothers' own milk is not a feasible option. Kenya has not yet established human milk banks (HMBs) for provision of safe DHM, which is free from any physical, chemical, microbiological contaminants or pathogens. This study aimed to establish the perceptions on donating and using DHM, and establishing HMBs in Kenya. Qualitative data were collected through 17 focus group discussions, 29 key informant interviews, and 25 in‐depth interviews, with women of childbearing age, community members, health workers, and policy makers. Quantitative interviews were conducted with 868 mothers of children younger than 3 years. Descriptive analysis of quantitative data was performed in STATA software, whereas qualitative interviews were coded using NVIVO and analysed thematically. Majority of them had a positive attitude towards donating breast milk to a HMB (80%) and feeding children on DHM (87%). At a personal level, participants were more willing to donate their milk to HMBs (78%) than using DHM for their own children (59%). The main concerns on donation and use of DHM were personal dislikes, fear of transmission of diseases including HIV, and hygiene concerns. Ensuring safety of DHM was considered important in enhancing acceptability of DHM and successful establishment of the HMBs. When establishing HMBs, Kenya must take into consideration communication strategies to address the main concerns raised regarding the quality and safety of the DHM. The findings will contribute to the development of HMB guidelines in Kenya and other African contexts.